Control of bacterial nitrate assimilation by stabilization of G-quadruplex DNA. Issue 92 (2nd November 2016) - Waller, Zoë A. E.; Pinchbeck, Benjamin J.; Buguth, Bhovina Seewoodharry; Meadows, Timothy G.; Richardson, David J.; Gates, Andrew J.
Abstract : Ligand-specific control of nitrate assimilation in Paracoccus denitrificans by stabilization of DNA G-quadruplex in the promoter region of nas . Abstract : Here we present a chemical-biology study in the model soil bacterium Paracoccus denitrificans, where we show ligand-specific control of nitrate assimilation. Stabilization of a G-quadruplex in the promoter region of the nas genes, encoding the assimilatory nitrate/nitrite reductase system, is achieved using known quadruplex ligands and results in attenuation of gene transcription.